2019
DOI: 10.1152/ajpheart.00206.2019
|View full text |Cite
|
Sign up to set email alerts
|

Macrophages and T cells in atherosclerosis: a translational perspective

Abstract: Atherosclerosis is now considered a chronic maladaptive inflammatory disease. The hallmark feature in both human and murine disease is atherosclerotic plaques. Macrophages and various T-cell lineages play a crucial role in atherosclerotic plaque establishment and disease progression. Humans and mice share many of the same processes that occur within atherogenesis. The various similarities enable considerable insight into disease mechanisms and those which contribute to cardiovascular complications. The apolipo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 122 publications
0
32
0
Order By: Relevance
“…Several types of immunoreactive cells are present throughout atherosclerosis formation including macrophages, T cells, B cells, mast cells and dendritic cells ( Figure 1 ). Despite the macrophages are the key cells in atherosclerosis ( 6 ), T cells are shown to be concerned with atherogenesis and especially T-cell subpopulations are suggested to trigger/dampen atherosclerotic inflammatory processes ( 7 ). Previous studies have showed that the pathogenesis of atherosclerosis is characterized by an imbalance between T-helper 1 (Th1) - and Th2-mediated immune functions ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several types of immunoreactive cells are present throughout atherosclerosis formation including macrophages, T cells, B cells, mast cells and dendritic cells ( Figure 1 ). Despite the macrophages are the key cells in atherosclerosis ( 6 ), T cells are shown to be concerned with atherogenesis and especially T-cell subpopulations are suggested to trigger/dampen atherosclerotic inflammatory processes ( 7 ). Previous studies have showed that the pathogenesis of atherosclerosis is characterized by an imbalance between T-helper 1 (Th1) - and Th2-mediated immune functions ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Th2-biased responses antagonize proatherogenic Th1 functions and thereby confer atheroprotection. Indeed, the role of the Th2 cells in the atherosclerotic process remains controversial and depends on the stage and site of the atherosclerotic lesion ( 7 , 12 ). The vast majority of studies have shown interleukin- (IL-) 17 contributed to the proinflammatory milieu of atherosclerosis ( 13 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…T cells are among the first cells to be recruited into atherosclerotic lesion. [79][80][81][82] The adaptive response is based on CD4 + and CD8 + T cells activation and antibody secretion by B cells. Once activated, CD4+ T cells multiply and differentiate into specialized effector T helper (Th) lymphocytes, while activated CD8+ T cells multiply and differentiate into cytotoxic CD8+ T lymphocytes.…”
Section: Role Of Adaptive Immunitymentioning
confidence: 99%
“…Th17 cells produce IL-17 which has different effects on lesions, emphasizing endothelial inflammation but also increasing fibrosis and promoting plaque stability. [79][80][81][82] Treg cells are immunoregulatory cells with atheroprotective properties: they secrete the immunosuppressive cytokines such as transforming growth factor-beta (TGF-β), IL-10 and IL-35, which exert anti-inflammatory actions. 83…”
Section: Role Of Adaptive Immunitymentioning
confidence: 99%
“…Atherosclerosis is responsible for several adverse and deadly vascular events such as coronary artery disease (CAD), myocardial infarction, and stroke (Bartlett et al., 2019). Activation or injury of endothelium is suggested to happen early in the course of the events (Mitra et al., 2017).…”
Section: Introductionmentioning
confidence: 99%